Petrocodon longitubus (Gesneriaceae), a new species from Guizhou, China - Li, Cong-Rui; Liu, Fang-Pu; Gadagkar, Sudhindra R.; Luo, Yang (Phytotaxa, 2019)
Petrocodon longitubus, a new species of Gesneriaceae from Guizhou province, China, is described and illustrated. It is similar to P. hunanensis in having four stamens, but readily differs in being rosulate and stemless and having a narrowly infundibuliform floral tube with the adaxial lip bending upward. Molecular evidence indicates that it is sister to P. hunanensis, but the two species differ markedly in morphology.